2021
DOI: 10.1080/13504851.2021.1971614
|View full text |Cite
|
Sign up to set email alerts
|

Investigating survivorship bias: the case of the 1918 flu pandemic

Abstract: Estimates of the effect of foetal health shocks may suffer from survivorship bias. The foetal origins literature seemingly agrees that survivorship bias is innocuous in the sense that it induces a bias towards zero. Arguably, however, selective mortality can imply a bias away from zero. In the case of the 1918 flu pandemic, a suppressed immune system may have been protective against the most severe consequences of infection. We use historical birth records from the maternity hospital of Bern, Switzerland, to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is consistent with the evidence from demographic studies on the population level for the USA, Scandinavian countries or Japan [ 20 25 ]. In the United States, it was found that increasing mortality rates from ILI in the population were associated with an increase in neonatal and infant mortality in the late 20 th century [ 49 ]. Depending on the trimester of exposure, various adverse pregnancy outcomes were also highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the evidence from demographic studies on the population level for the USA, Scandinavian countries or Japan [ 20 25 ]. In the United States, it was found that increasing mortality rates from ILI in the population were associated with an increase in neonatal and infant mortality in the late 20 th century [ 49 ]. Depending on the trimester of exposure, various adverse pregnancy outcomes were also highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…A possible increase in miscarriage risk due to exposure to influenza during the first trimester would have gone unnoticed because it was underreported. Thus, we do not have information on unobserved fetal loss early in pregnancy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example of studying the survivorship bias is paper [5], in which the positive effect of a suppressed immune system on protection against the most severe consequences of infection was investigated. At the same time, it should be emphasized that the work does not provide a procedure for eliminating the error of the one who survived on one side.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%